0825 Sleep and Social Emotional Functioning among Children from Families with Child Protective Services Involvement. (27th April 2018) - Hash, J; Fleming, C; Oxford, M
Abstract: Introduction: This study longitudinally examined sleep problems, naps, and social emotional functioning among children from families with a Child Protective Services (CPS) maltreatment report. Methods: This was a secondary analysis of a longitudinal study including 123 parent-child dyads (child age 10–24 months at baseline) involved with CPS. Every three months from baseline (T1) to nine-months post-baseline (T4), parents reported about children's externalization, internalization, and competence on the Infant-Toddler Social Emotional Assessment (higher scores = higher externalization, internalization, competence ). At T2, parents indicated if their child took daily naps (0 = no, 1 = yes) and if they had a sleep problem (0 = no, 1 = yes) on a modified Brief Infant Sleep Questionnaire. Conditional intercept and slope growth models were tested for externalization and internalization, controlling for baseline age and gender. T1 externalization and internalization were entered to predict T2 naps and sleep problems, which were then entered to predict growth in T2-T4 (slope) and level of T4 (intercept) externalization and internalization. Multiple linear regression examined T4 competence as predicted by T2 naps and sleep problems, controlling for baseline age, gender and competence. Results: Fit was excellent for the externalization and internalization models ( 2 s non-significant; RMSEAs = 0.00). Children with higher T1 externalization were significantly more likely to have a T2 sleep problem ( ß = 0.24, SE = 0.12). Children with a T2 sleep problem and who did not take daily T2 naps had significantly higher levels of T4 externalization ( ß = 0.32, SE = 0.09 and ß = -0.34, SE = 0.17, respectively) and T4 internalization ( ß = 0.36, SE = 0.13 and ß = -0.46, SE = 0.17, respectively). Children who took daily T2 naps had significantly higher T4 competence ( ß = 0.20, SE = 0.09). Conclusion: Sleep problems and daily napping behaviors may serve as early indicators of later social emotional functioning, and externalizing problems may heighten risk of later sleep problems among young children with CPS involvement. Support (If Any): NICHD grants R01 HD061362 and U54HD083091; University of Washington Magnuson Scholarship.